Pengaruh Pelaksanaan Ujian Akhir Semester Berbasis Komputer Terhadap Motivasi dan Kedisiplinan Belajar Siswa Kelas XII IPA SMA Negeri 3 Sorong - Stefany Margareta Martono; Menik Wijayanti (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2021)
State Senior High School 3 (SMA N 3) Sorong is one of the schools in the city of Sorong which since 2016 has been implementing Computer-Based Semester Final Examinations. However, since the implementation of the computer-based UAS was based on the results of the achievement survey, in this case, the test scores obtained by students were not so good during the last few years. Samples were taken from a population of 310 students and based on the Harry King Nomogram with a 95% confidence interval, the number of samples taken was 143 students. The method used in this research is quantitative descriptive method. The purpose of this research was to find the effect of the implementation of computer-based final semester exams on the motivation and learning discipline of students of class XII IPA SMA Negeri 3 Sorong. The results showed: 1) There was no significant effect of the implementation of computer-based UAS with the learning motivation of students of class XII IPA SMA Negeri 3 Sorong, 2) There was a significant effect of the implementation of computer-based UAS with the learning discipline of students of class XII IPA SMA Negeri 3 Sorong.